Penerapan syariat Islam melalui Selametan sebagai ‎tradisi akulturatif dalam konteks pernikahan berbasis ‎weton - Fanani, Muhammad Fithrah (Maliki Interdisciplinary Journal, 2023)
The custom of calculating weton in marriages in Indonesia is still used in this modern era. Many marriages then have to be canceled due to incompatibility of weton between partners. Based on this, the purpose of this study is to discuss practical solutions carried out by the Javanese community, namely the ritual or ceremony of greeting couples with different weton from the perspective of Islamic law. From the results of the research, it is known that the salvation ritual includes something or a ceremony that is carried out by inviting relatives, neighbors and people around which is carried out through several activities or methods such as giving banquets to the invitees, visiting neighbors and people around with the aim is to strengthen brotherhood, and by reading various mantras or prayers that have the goal of achieving prosperity, peace, blessings, and harmony in the household of married couples who have different concepts of weton calculations. However, there are no specific prohibitions regarding the implementation of these rituals. In the context of Islamic law, slametan is included in the activity of alms which is sunnah. Because the concept of the ceremony or ritual of salvation has a close relationship and is interrelated with Islamic sharia law and customary law.